Early Liver Transplantation in Acute Alcoholic Hepatitis - Haugen, Christine E.; Cameron, Andrew M. (Seminars in Liver Disease, 2020)
Alcohol-related liver disease (ALD) is currently the leading indication for liver transplantation in the United States. Among patients with ALD, those with acute alcoholic hepatitis who do not respond to medical treatment have a 6-month mortality of 70% without transplantation. Despite the high mortality, the majority of patients will not be eligible for transplant, given that most centers follow the 6-month abstinence rule. A handful of centers in Europe and the United States perform early liver transplantation (< 6 months abstinence) in these patients, as it provides a substantial survival benefit. Short-term outcomes for these recipients are favorable, and relapse rates parallel those seen in alcoholic cirrhosis transplant recipients who have completed the 6-month wait period. Moving forward, studies examining long-term outcomes and candidate selection are necessary for this growing subset of liver transplant candidates.
Keywords: liver transplant; alcoholic hepatitis; liver disease